OAT BREEDING IN THE KUBAN REGION - T. E. Kuznetsova; S. A. Levshtanov; N. V. Serkin (Труды по прикладной ботанике, генетике и селекции)
The article presents the history of oat breeding in the Kuban region. Two varieties of spring oats ‘Desant’ and ‘Assol’ have been developed and submitted for the state trials. New varieties are described in detail.